(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
In order to simulate the intricate stress distribution into important locations, Full-scale components, undergo fatigue testing. Parts of a larger structural system, such as sub-assemblies, are sometimes the subjects of these tests. Lastly, they are often performed on little samples with the purpose of collecting fatigue data. This data shows how a material has been affected by factors including stress level, surface preparation, environment, and loading history.